Контроль и диагностирование оборудования прокатного производства - Богаенко И. Н. Иван Николаевич; Донченко В. И. Валерий Иванович; Савченко Ю. Г. Юлий Григорьевич; Ушаков В. А. Виктор Александрович (Киев, Технiка, 1982)
Авт. указаны в вып. дан.